Natural Selection Equally Supports the Human Tendencies in Subordination and Domination: A Genome-Wide Study With in silico Confirmation and in vivo Validation in Mice - Chadaeva, Irina; Ponomarenko, Petr; Rasskazov, Dmitry; Sharypova, Ekaterina; Kashina, Elena; Kleshchev, Maxim; Ponomarenko, Mikhail; Naumenko, Vladimir; Savinkova, Ludmila; Kolchanov, Nikolay; Osadchuk, Ludmila; Osadchuk, Alexandr (Frontiers in Genetics, 2019)
We proposed the following heuristic decision-making rule: “IF an excess of a protein relating to the nervous system is an experimentally known physiological marker of low pain sensitivity, fast postinjury recovery, or aggressive, risk/novelty-seeking, anesthetic-like, or similar agonistic-intolerant behavior AND IF a single nucleotide polymorphism (SNP) causes overexpression of the gene encoding this protein THEN this SNP can be a SNP marker of the tendency in dominance WHILE underexpression corresponds to subordination AND vice versa.” Using this decision-making rule, we analyzed 231 human genes of neuropeptidergic, non-neuropeptidergic, and neurotrophinergic systems that encode neurotrophic and growth factors, interleukins, neurotransmitters, receptors, transporters, and enzymes. These proteins are known as key factors of human social behavior. We analyzed all the 5,052 SNPs within the 70 bp promoter region upstream of the position where the protein-coding transcript starts, which were retrieved from databases Ensembl and dbSNP using our previously created public Web service SNP_TATA_Comparator (http://beehive.bionet.nsc.ru/cgi-bin/mgs/tatascan/start.pl). This definition of the promoter region includes all TATA-binding protein (TBP)-binding sites. A total of 556 and 552 candidate SNP markers contributing to the dominance and the subordination, respectively, were uncovered. On this basis, we determined that 231 human genes under study are subject to natural selection against underexpression (significance p < 0.0005), which equally supports the human tendencies in domination and subordination such as the norm of a reaction (plasticity) of the human social hierarchy. These findings explain vertical transmission of domination and subordination traits previously observed in rodent models. Thus, the results of this study equally support both sides of the century-old unsettled scientific debate on whether both aggressiveness and the social hierarchy among humans are inherited (as suggested by Freud and Lorenz) or are due to non-genetic social education, when the children are influenced by older individuals across generations (as proposed by Berkowitz and Fromm).